2021
DOI: 10.53911/jae.2021.12208
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bio-fertilizers on growth and yield of spinach (Beta vulgaris L.) cv. All Green

Abstract: Spinach beet is one of the most common leafy vegetables of tropical and sub-tropical regions. The popular palak growing states include Uttar Pradesh, West Bengal, Maharashtra and Gujarat. However, Palak is not very popular in South India. It is primarily used as potherb. It is a rich Source of vitamin A and C and also contains appreciable amount of protein, calcium and iron. The leaves contain low oxalic acid. Variety All Green was developed at the Indian Agricultural Research Institute, New Delhi, it produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…The more availability of nutrients under higher levels might have encouraged the photosynthesis, accumulation of food material and higher plant growth resulting in more plant height. These results are in accordance with the findings of Ali et al [10], Singh et al [11] and Hashimi et al [12].…”
Section: Plant Heightsupporting
confidence: 93%
“…The more availability of nutrients under higher levels might have encouraged the photosynthesis, accumulation of food material and higher plant growth resulting in more plant height. These results are in accordance with the findings of Ali et al [10], Singh et al [11] and Hashimi et al [12].…”
Section: Plant Heightsupporting
confidence: 93%
“…These findings are in line with the findings of Wange et al [8] and Tripathi et al [9]. The increase in yield might be due to increased fruit set per plant, due to the fact that nitrogen fixers and phosphorous solubilize not only increased the availability of nitrogen and phosphorous to the plants but also increased their translocation from root to flower through plant foliage [10]. Similar results were reported by Mirza Khan et al [11] in safflower and Poonia and Dhaka [12] in tomato.…”
Section: Yield Parameterssupporting
confidence: 91%
“…These results are consistent with those of Wange et al [8] and Tripathi et al [9], who found that applying Azotobacter and PSB increased strawberry yield. While nitrogen fixers and phosphorus solubilizers boosted the availability of nitrogen and phosphorus to the plants as well as their transfer from root to flower through plant foliage, the rise in yield may be attributable to an increase in fruit set per plant [10]. Similar findings in safflower and tomatoes were reported by Mirza khan et al [11] and Poonia and Dhaka [12], respectively.…”
Section: Yield Parameterssupporting
confidence: 71%
“…The International Council on Medical Research (ICMR) states that an individual needs between 50 and 60 grammes of leafy vegetables per day. Our country produces about 19.7 tonnes per hectare, a significant decrease from other wealthy countries like Spain, whose production is 39.3 tonnes per hectare [7]. When growing baby spinach, organic fertilisers such farmyard manure, goat and chicken dung, and biofertilizers can take the place of chemical fertilisers [8].…”
Section: Introductionmentioning
confidence: 98%